Pro SQL Server 2008 Policy-Based Management - Simmons, Ken.; Stasiuk, Colin; Segarra, Jorge; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Pro SQL Server 2008 Policy-Based Management is critical for database administrators seeking in-depth knowledge on administering servers using the new policy-based management features introduced in SQL Server 2008. This book will cover everything from a basic introduction to policy-based management to creating your own custom policies to enforce consistent rules across your organization. Provides in-depth treatment of policy-based management in a single source Provides practical usage scenarios for policy-based management Provides guidance to help meet growing regulatory compliance needs
to Policy-Based Management -- Creating Policies -- Evaluating Policies -- Policy-Based Management Using PowerShell -- Receiving Alerts for Policy Violations -- Policy-Based Management Internals -- Practical Uses of Policy-Based Management -- Reporting -- Enforcing Compliance -- Where to Go from Here.
Keywords: Computer science; Computer Science; Programming Techniques